Temperature monitoring using polymer optical fiber with integration to the internet of things - Hazura Haroon; Siti Khadijah Idris; Anis Suhaila Mohd Zain; Hanim Abdul Razak; Fauziyah Salehuddin (Bulletin of Electrical Engineering and Informatics, 2021)
In this paper, a polymer optical fiber (POF) is applied for temperature measuring of water solution using a light source of 650nm. The aim is to analyse the impact of temperature variations on the output of POF sensor device in terms of output power and sensitivity. From the study, the POF sensor shows a linear trend when the temperature is increased from 30°C to 80°C with the sensitivity of the polymer optical fiber for output power to the temperature are 0.00973 dBm/°C or 0.14797 nW/°C, for optical characterization and 0.0011 V/°C for electrical characterization. The integration of the Internet of Things to the system helps the user to monitor the temperature of various spaces anywhere at any time. The sensed values are controlled by Arduino Uno R3 and then sent to Blynk to provide wireless monitoring by the user.